PENGUNGKAPAN DIRI SISWA DALAM MENGIKUTI LAYANAN KONSELING KELOMPOK (STUDI KASUS DI MAN MODEL PALANGKARAYA) - Dudi, Josef (Universitas Muria Kudus, 2017)
The research was conducted in MAN Model Palangkaraya. Qualitative research approaches and case study. Subjects in this study is teacher guidance and counseling 2 (two) people and students 7 (seven) people. Analysis of the data in the research include covering reduction, a data display, and conclusion drawing / verification. The purpose of this research is to Knowing Self Disclosure Students In Following Group Counseling. The results showed that self Disclosure refers to the communication behavior in which someone expresses aspects of themselves with personal information, experiences, personal thoughts and personal feelings. The group leader is obliged to convince group members that whatever is discussed in groups counseling will be kept confidential. In group counseling, confidentiality is the basic problem that is most important.